2020
DOI: 10.3390/make3010002
|View full text |Cite
|
Sign up to set email alerts
|

Understand Daily Fire Suppression Resource Ordering and Assignment Patterns by Unsupervised Learning

Abstract: Wildland fire management agencies are responsible for assigning suppression resources to control fire spread and mitigate fire risks. This study implements a principle component analysis and an association rule analysis to study wildland fire response resource requests from 2016 to 2018 in the western US to identify daily resource ordering and assignment patterns for large fire incidents. Unsupervised learning can identify patterns in the assignment of individual resources or pairs of resources. Three national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The IMSR is a valuable data source for both fire managers and researchers 25 , and we have seen efforts to obtain and use several pieces of IMSR information in research including the PL 26 , 27 and suppression resource use 28 30 . However, we are unaware of other efforts to generate a research-ready version of the IMSR archive, which would support broader use of these data.…”
Section: Background and Summarymentioning
confidence: 99%
“…The IMSR is a valuable data source for both fire managers and researchers 25 , and we have seen efforts to obtain and use several pieces of IMSR information in research including the PL 26 , 27 and suppression resource use 28 30 . However, we are unaware of other efforts to generate a research-ready version of the IMSR archive, which would support broader use of these data.…”
Section: Background and Summarymentioning
confidence: 99%
“…Resource use on large fires (e.g., Hand et al, 2017) and comparisons between resource use on a geographical scale (e.g., Wei et al, 2020) has also been examined; but there remains a need for further understanding of the decision-making concerning airtanker IA dispatch because resource allocation during this stage can be costly but can contribute to rapid containment. Taylor and Nadeem (2022) recently examined factors which resulted in the dispatch of airtankers on IA on fires in British Columbia, Canada, and found that the average projected FWI over the next three days was a good indicator of such airtanker use.…”
Section: Introductionmentioning
confidence: 99%